REPRESENTASI HOMOSEKSUALITAS DI YOUTUBE: (Studi Semiotika pada Video Pernikahan Sam Tsui) - Lilis Rucirisyanti; Redi Panuju; Daniel Susilo (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Social media is instrumental in giving effect to nitizens, good effects or bad effect, then social media can be also represent a person. Diserve social media make it interesting for nitizens. One of social media is Youtube. Many a lot of video at there, strat from tips and trick videos, journey or vacation video, wedding video, and ect. Everyone can publish their video on Youtube. No exception of same sex enthusiast, in this study are homosexual or gay. One of is a wedding video Sam Tsui and Casey Braves. This research is a qualitative research and this research uses semiotcs analysus of Roland Barthes. By doing an analysis of video that have been published by Sam on Youtube, also do document search and literature. The author sees the existence of verbal and non vebal forms of representation from same sex merriage video of men and men. Key words : Representation, gay, homosexual, social media, Youtube, merriage.